Bat - Arnold, Caroline; Hewett, Richard (New York : Morrow Junior Books, 1996)
Discusses the physiology and behavior of this mammal as well as the fears, misconceptions, and superstitions which have given it a bad reputation.
Includes index.
Wilson's Children.
Elem. School Library Collection.
School Library Journal.
5.2
3-6
Keywords: Bats -- Juvenile literature; Bats; Bats; Bats